LEGAL PROTECTION OF THE CONSUMER IN THE HOUSING SALE AND PURCHASE AGREEMENT - M Lutfi (University of Sang Bumi Ruwa Jurai, 2020)
The type of research in this research is descriptive normative research, the approach used is, juridical normative and empirical approaches. The data used in this research comes from primary data and secondary data, and tertiary legal materials. Data collection data classification systematization of research data using qualitative descriptive data analysis. The results of research and discussion of the aspects of consumer protection in the housing sale agreement can be seen that the aspects of housing consumer protection consist of three stages, namely the pre-transaction stage, the transaction stage, and the post-transaction stage. Consumers who have suffered losses rarely report their losses to the authorities and authorities. Nerimo culture in Indonesian society. Consumers' strenuous effort to defend their rights. Law enforcement officers who are not firm. Lack of community participation. Low legal awareness of producers and consumers.